The influence of relative values of outside director stock options on firm strategic risk from a multiagent perspective - Lim, Elizabeth N. K.; Mccann, Brian T. (Strategic Management Journal, 2013)
Prior work has examined the effects of absolute levels of outside director stock option grants on risk behavior without recognizing that relative stock option values could differentially affect risk taking. Drawing from the house money effect perspective, we extend this literature by examining how positive deviation from prior outside director option grants values influences firm strategic risk. Additionally we draw from the behavioral agency model and the power literature to develop a multiagent contingency framework suggesting the effect of positive director pay deviation depends on the incentives and power of CEOs reflected in CEO stock ownership and CEO duality, respectively. Our empirical results indicate positive pay deviation has a positive effect on firm risk taking while high ownership and duality independently and jointly weaken this base relationship . Copyright © 2013 John Wiley & Sons, Ltd.